2022
DOI: 10.1088/1741-4326/ac5f18
|View full text |Cite
|
Sign up to set email alerts
|

On suitable experiments for demonstrating the feasibility of the beam-driven plasma neutraliser for neutral beam injectors for fusion reactors

Abstract: Plasma neutralisers promise increased neutralisation efficiency of negative ion beams in neutral beam injection (NBI) beamlines compared with gas neutralisers. It has been suggested that, in the presence of an electron-confining magnetic cusp field along all neutraliser walls, the beam itself could ionise the neutraliser gas sufficiently to take advantage of this effect, avoiding the added complexity of external power coupling to the neutraliser. These predictions come from a zero-dimensional model by Surrey and Holm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…• For every allowed point in the discretized parameter space from above the plasma density and neutral gas temperature in the BDPN is calculated using a parametrized scaling obtained with Starnella's model [7]. This calculation is carried out for various gas flows into the neutralizer.…”
Section: Problem Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…• For every allowed point in the discretized parameter space from above the plasma density and neutral gas temperature in the BDPN is calculated using a parametrized scaling obtained with Starnella's model [7]. This calculation is carried out for various gas flows into the neutralizer.…”
Section: Problem Setupmentioning
confidence: 99%
“…In order to obtain the ionization degree and neutral gas temperature, the BDPN model of Starnella et al [7] would have to be run for every point in the parameter space exploration described above. Starnella's code is a zero-dimensional balance code that models the various populations of ions and electrons with their numerous interactions and loss channels (such as wall losses, impact dissociation, dissociative recombination, etc.)…”
Section: The Bdpn Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…A neutralization efficiency of about 75% can be reached in comparison to the 55% achieved by a gas neutralizer, relaxing thus the demands on the accelerated ion current at same beam power or increasing the beam power from one beam line. Recent investigations on the efficiency of the BDPN revealed that there is a need to benchmark the simulations by experimental investigations [23]. Uncertainties concern the plasma confinement in the magnetic cusp field, the achievable electron density and thus ionization degree being together with the gas temperature the key parameters to be benchmarked.…”
Section: Beam Driven Plasma Neutralizer (Bdpn)mentioning
confidence: 99%
“…Uncertainties concern the plasma confinement in the magnetic cusp field, the achievable electron density and thus ionization degree being together with the gas temperature the key parameters to be benchmarked. Studies showed that present day experimental facilities have either not the required beam power to ionize the gas sufficiently or are not available yet [23]. Therefore, a proof-of-principle setup is under consideration in which the stripped electrons of 42 A are mimicked by electrons generated by a filament at the required energy of 272 keV.…”
Section: Beam Driven Plasma Neutralizer (Bdpn)mentioning
confidence: 99%